Integration of Moderate Religious Values into the Educational Curriculum at Pesantren-Based Madrasah Tsanawiyah - Ahmad Zubaidi; Vinda Khairus Soleha (Jurnal Ilmiah Profesi Pendidikan, 2026)
Religious moderation has become a strategic agenda in Islamic education, particularly in pesantren-based madrasas that integrate formal schooling with traditional religious culture. This study aims to analyze how values of religious moderation are integrated into Pesantren-based Madrasah Tsanawiyah (MTs) through the interaction of the formal curriculum, teacher strategies, and pesantren culture as a hidden curriculum. Employing a qualitative research design, the study was conducted at MTs Negeri 1 Probolinggo using interviews, observations, and document analysis as data collection techniques. The findings reveal four main points: (1) the formal curriculum provides a normative and structural framework for embedding religious moderation values; (2) teacher strategies play a central role in internalizing these values through exemplary behavior and contextual pedagogical approaches; (3) pesantren culture functions as a hidden curriculum that continuously reinforces moderation values through daily practices, traditions, and social interactions; and (4) the integration of religious moderation values occurs in a cyclical and interconnected process rather than a linear one. In conclusion, the study demonstrates that the effective integration of religious moderation in pesantren-based madrasas requires a synergistic relationship between curriculum design, pedagogical practice, and institutional culture to ensure the sustainability of moderate religious values.